INVESTIGATING THE RELATIONSHIP BETWEEN DAILY SPIRITUAL EXPERIENCE AND CANCER PATIENTS RESILIENCE EXTENT IN IMAM KHOMEINI HOSPITAL OF TEHRAN, 2016 - Nazanin Savaryand; Nazi Savary, (The Malaysian Journal of Nursing (MJN), 2019)
Investigating the relationship between daily spiritual experience and cancer patients' resilience in Imam Khomeini Hospital of Tehran, 2016. Introduction: Reinforcing resilience is one of the effective ways of encountering and dealing with chronic diseases like cancer. Identifying the influential factors on cancer patients’ resilience has a significant impact on decreasing this disease effects. From among these factors is daily spiritual experience. Therefore, the purpose of this study is to investigate the relationship between daily spiritual experience and cancer patients' resilience at Imam Khomeini hospital of Tehran, 2016. Method: This study was conducted through a descriptive correlational method among 234 cancer patients visiting Imam Khomeini Hospital of Tehran from September 2016 to May 2017 was included in this study. They were selected through easy Sampling Techniques. Instruments used for collecting data were reliable and valid questionnaires of personal demographic characteristics, resilience scale of Connor & Davidson (2003) and Underwood & Teresi (2002) scale of daily spiritual experience. The data were then analyzed in their significant levels using inferential and descriptive statistics such as Pierson correlation coefficient, multiple regression coefficient and variance analysis using 19th version of SPSS software. Findings: Most of participants of the study were more than 50 years old (40.3%) and married (37.5%) with a diploma degree. There is no significant relationship between mean of daily spiritual experience of the patients and their resilience in terms of their marital state and level of education (p>0.05). Mean of scores of daily spiritual experience and patients’ resilience was more than the average extent (62.24 and 57, respectively). There was a significant relationship between resilience and daily spiritual experience (p=0.002). According to multiple regression analysis, the best predictor for patients' resilience was the dimension of Connection to God from daily spiritual experience and 1.9% of variance signifies the resilience. Conclusion: Concerning the role of daily spiritual experience in increasing resilience, it is recommended to plan a necessary program in order for doing interventions related to spirituality by head nurses so that the patients could be able to get along with their disease by enhancing their resilience.